1999
DOI: 10.1007/s004150050476
|View full text |Cite
|
Sign up to set email alerts
|

Truths, errors, and lies around “reflex sympathetic dystrophy” and “complex regional pain syndrome”

Abstract: The shifting paradigm of reflex sympathetic dystrophy-sympathetically maintained pains-complex regional pain syndrome is characterized by vestigial truths and understandable errors, but also unjustifiable lies. It is true that patients with organically based neuropathic pain harbor unquestionable and physiologically demonstrable evidence of nerve fiber dysfunction leading to a predictable clinical profile with stereotyped temporal evolution. In turn, patients with psychogenic pseudoneuropathy, sustained by con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 24 publications
0
21
0
5
Order By: Relevance
“…These observations in connection with normal neurophysiological test results in CRPS I led to the hypothesis that CRPS is primarily a psychogenic disorder. 122,123 However, well designed studies and comprehensive reviews of the available literature have suggested that psychological symptoms are the result and not the cause of CRPS.…”
Section: Psychology Of Crpsmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations in connection with normal neurophysiological test results in CRPS I led to the hypothesis that CRPS is primarily a psychogenic disorder. 122,123 However, well designed studies and comprehensive reviews of the available literature have suggested that psychological symptoms are the result and not the cause of CRPS.…”
Section: Psychology Of Crpsmentioning
confidence: 99%
“…137,151 Some authors even discard the concept that the sympathetic nervous system is actively involved in the generation of pain. 122,152 They claim that interventions that block sympathetic activity lack speci®city, and argue that the techniques and results of sympathetic blockade have rarely been adequately evaluated and are in most cases not placebo-controlled.…”
Section: Pain In Crps G Wasner Et Almentioning
confidence: 99%
“…Hierbei sind depressive und Angststörungen am häu-figsten, so dass eine entsprechende psychologische Betreuung wichtig ist. Einige Untersucher behaupten, dass es sich beim CRPS insgesamt um eine psychogene Erkrankung handelt, zumal sich neurophysiologisch keine Auffälligkeiten finden [99,141] Neben der klinischen Untersuchung gibt es technische Zusatzuntersuchungen, die ergänzende diagnostische Informationen über die autonomen,motorischen und sensiblen Störungen liefern, ohne dass bisher ein diagnostischer Goldstandard existiert.…”
Section: Psychische Faktorenunclassified
“…Finally, the objective signs in those patients, typically labeled "RSD" (reflex sympathetic dystrophy), are nonspecific and explainable otherwise. When the concept of SMP collapsed, it carried with it the concept of "RSD" [11,12].…”
Section: Hypothetical Mechanisms Of Neuropathic Pain: a Brief Historymentioning
confidence: 99%